Analisis Kearifan Lokal Tradisi Sako Seng Pada Masyarakat Sikka Dalam Perspektif Filsafat Anti Kekerasan Mahatma : Analysis of the Local Wisdom of the Sako Seng Tradition in the Sikka Community from the Perspective of Mahatma's Philosophy of Anti-Violence - Reu, Yosep Hendrikus; Hayong, Bernardus Subang (Jurnal Filsafat Indonesia, 2025)
Sako seng tradition is one of the local wisdom and cultural heritage of the Sikka people, East Nusa Tenggara. The principles of mutual cooperation, solidarity and peace in jointly cultivating agricultural land are unique to this tradition. However, the development of modernity and advances in agricultural technology bring challenges and obstacles to the preservation of this tradition, especially with the emergence of individualistic work patterns and the declining participation of the younger generation. This study examines the relevance of Mahatma Gandhi's thoughts, especially the principle of non-violence (ahimsa), and collective work as a philosophical foundation for the revitalization of sako seng as a distinctive tradition of the Sikka people. Gandhi's thought has a close correlation to this tradition as it emphasizes the importance of social change through peaceful means and collective consciousness, which is in line with the spirit of sako seng which rejects violence and prioritizes mutual cooperation. This research uses interviews and literature study methods. The results of this study show that an attitude of adaptation to the development of modernity and technology is necessary to maintain the spirit of solidarity and mutual cooperation of the Sikka community. In addition, policy support and community awareness, especially for the younger generation, determine the sustainability of the sako seng tradition. The integration of Gandhian values and local traditions not only enriches local heritage, but also becomes a moral foundation in building a harmonious and sustainable society amidst the changing times. Revitalizing the sako seng tradition is not only a matter of cultural enrichment but also ethical renewal in the face of modernity.